Landscape and Earth in Early Modernity : Picturing Unruly Nature. - Göttler, Christine (Amsterdam University Press, 2022)
Early modern views of nature and the earth upended the depiction of land. Landscape emerged as a site of artistic exploration at a time when environments and ecologies were reshaped and transformed. This volume historicizes the contingency of an ever-changing elemental world, reframing and reimagining landscape as a mediating space in the interplay between the natural and the artificial, the real and the imaginary, the internal and the external. The lens of the "unruly" reveals the latent landscapes that undergirded their conception, the elemental resources that resurfaced from the bowels of the earth, the staged topographies that unsettled the boundaries between nature and technology, and the fragile ecologies that undermined the status quo of human environs. Landscape and Earth in Early Modernity: Picturing Unruly Nature argues for an art history attentive to the vicissitudes of circumstance and attributes the regrounding of representation during a transitional age to the unquiet landscape.
Description based upon print version of record.
Keywords: Landscapes in art.; Nature in art.; Paysages dans l'art.; Nature dans l'art.; Renaissance art.; Early modern history: c 1450/1500 to c 1700.; ART / History / Renaissance.; Landscapes in art; Nature in art; History of art.; Landscapes / seascapes.; European history: Renaissance.; Art History, Early Modern, Landscape, Seascape, Nature.